Initial experience with SphinKeeper™ intersphincteric implants for faecal incontinence in the UK: a two‐centre retrospective clinical audit. (22nd September 2020) - Leo, C. A.; Leeuwenburgh, M.; Orlando, A.; Corr, A.; Scott, S. M.; Murphy, J.; Knowles, C. H.; Vaizey, C. J.; Giordano, P.
Abstract: Aim: The SphinKeeper™ artificial bowel sphincter implant is a relatively new surgical technique for the treatment of refractory faecal incontinence. This study presents the first experience in two UK tertiary centres. Method: This is a retrospective audit of prospectively collected clinical data in relation to technique, safety, feasibility and short‐term effectiveness from patients undergoing surgery from January 2016 to April 2019. Baseline data, intra‐operative and postoperative complications, symptoms [using St Mark's incontinence score (SMIS)] and radiological outcomes were analysed. Results: Twenty‐seven patients [18 women, median age 57 years (range 27–87)] underwent SphinKeeper. In 30% of the patients, the firing device jammed and not all prostheses were delivered. There were no intra‐operative complications and all patients were discharged the same or the following day. SMIS significantly improved from baseline [median −6 points (range −12 to +3); P  < 0.00016] with 14/27 (51.9%) patients achieving a 50% reduction in the SMIS score. On postoperative imaging, a median of seven prostheses (range 0–10) were identified with a median of five (range 0–10) optimally placed. There was no relationship between number of well‐sited prostheses on postoperative imaging and categorical success based on 50% reduction in SMIS ( χ 2 test, P  = 0.79). Conclusion: SphinKeeper appears to be a safe procedure for faecal incontinence. Overall, about 50% patients achieved a meaningful improvement in symptoms. However, clinical benefit was unrelated to the rate of misplaced/migrated implants. This has implications for confidence in proof of mechanism and also the need for technical refinement.